Penglibatan komuniti dalam Program Pembangunan Luar Bandar: kajian kes di Pusat Pertumbuhan Desa Gedong, Sarawak. - Haslina Hashim,; Regina Garai Abdullah, (Universiti Kebangsaan Malaysia, 2009)
This article discusses the issues of community participation with special reference to the Rural Growth Centre (RGC) programme in Sarawak. The RGC is aimed at creating growth centres which are self-sufficient and equipped with the infrastructure, economic, service centre and human capital components. The establishment of an RGC involves large financial obligation and local community participation is essential in ensuring its success. Hence, this article examines the community perceptions regarding their participations in RGC development, specifically looking at RGC Gedong, one of the earliest RGCs established in Sarawak, as the case study area. The article also looks at the extent to which the community participates in the implementations of RGC Gedong and its impacts in terms of improving the community’s quality of life. In addition, community participations are discussed using Pretty’s typology of participation and Arnstein’s Ladder of Participation Model. It is found that the level of community participation in RGC Gedong is very low and it is categorised as passive participation (Pretty’s Typology) and participation as therapy (Arnstein’s Model), despite the fact that it should have been classified as partnership participation. This discrepancy exists due to lack of transparency in decision making, lack of information given to the community as well as the lack of control (or power) on the part of the community in the decision making process. All these have resulted in the lack of active community participations, which actually hinder the development of RGC Gedong. It can be considered as a failed initiative as it did not achieve all its goals and one of the contributing factors is the failure to involve the community in the development process.